The disappearance of the social in American social psychology - Greenwood, John D (Cambridge University, 2013)
The Disappearance of the Social in American Social Psychology is a critical conceptual history of American social psychology. In this challenging work, John Greenwood demarcates the original conception of the social dimensions of cognition, emotion, and behavior, and of the discipline of social psychology itself, that was embraced by early twentieth-century American social psychologists.